POLA PENDIDIKAN KITA, APA YANG SALAH - Alpiyanto Alpiyanto; Fajri Ismail (Ta'dib: Jurnal Pendidikan Islam, 2012)
Ideals to the intellectual life of the nation by order of value as thefoundation of ethics and moral domains of intelligence and skill has beendisoriented. It can be seen from the culture of corruption that stillplagued the country, beating punishment of journalists that was hitby students of SMAN 6 Jakarta, clashes among students in Lampung, clashes among residents in different regions and the church bombing inSolo. Therefore, this study wanted to find out what went wrong to educationthat has been implemented so far. This study is a case study of thepatterns which are applied during this study. The study results showed that theeducation that has been implemented so far seems to be concerned with the logicrather than feelings (language of heart) so it is suggested that it is important to educate the heart rather than logic.